A pitfall of using offer quantity limits. Issue 3 (27th May 2021) - Carlson, Jay P.
ABSTRACT: Retailers may wish to foster high, but not excessively high, consumer purchase quantities of a product. Purchase quantity limits can be used to try to walk that fine line. Two commonly used approaches that retailers use to express purchase quantity limits – offer quantity limits and unit quantity limits – are studied in a setting where a product is offered for a discounted price. An example of a unit quantity limit (UQL) is 'Limit 2, ' which simply restricts the consumer to a maximum purchase of two units of the discounted product. An offer quantity limit (OQL) of 'Limit 2 Offers, ' for example, allows the consumer to take advantage of the presented price deal a maximum of two times. Since the price information may specify two or more units, the maximum number of units consumers are allowed to purchase when an OQL is present cannot be determined solely from the number included in the OQL verbiage – the price information must also be considered. A pilot experimental study and main experiment provide evidence strongly suggesting that consumers misunderstand OQLs. The fallacy would harm retailers desiring to stimulate high consumer purchase quantities from a promotion that includes a restriction. Specifically, consumers intend to purchase fewer units when confronted with an OQL rather than an equivalent UQL when one of the two restrictions is imposed on a multiple unit price promotion. This effect is attenuated when the numeric value of the OQL is not a multiple of the units in the price information. The present research is the first to examine how consumers react to OQLs relative to UQLs.